(untitled) (Journal of Health, Population and Nutrition, 2012)
Eosinophilic fasciitis is an uncommon disorder of unknown aetiology and poorly-understood pathogenesis. Since 1974, over 250 cases of eosinophilic fasciitis have been reported worldwide. The first case of eosinophilic fasciitis from Bangladesh is reported here. The challenges of diagnosis, treatment, and follow-up, including family and social support, are discussed. DOI: http://dx.doi.org/10.3329/jhpn.v30i1.11292 J HEALTH POPUL NUTR 2012 Mar;30(1):117-120